Characterization of Oily and Non-Oily Natural Sediments in Palm Oil Mill Effluent - Reem A. Alrawi; Nik Norulaini Nik Ab Rahman; Anees Ahmad; Norli Ismail; A. K. Mohd Omar (Journal of Chemistry)
Palm oil is one of the many vegetable oils widely consumed around the world. The production of palm oil requires voluminous amount of water with the concurrent generation of large amount of wastewater known as palm oil mill effluent (POME). POME is a mixture of water, oil, and natural sediments (solid particles and fibres).There is a dearth of information on the physical properties of these POME sediments. This study intends to distinguish the physical properties of oily and non-oily POME sediments which include sediment size, particle size distribution (PSD), sediment shape, sediment surface morphology, and sediment density. These characterizations are important for future researches because these properties have significant effects on the settling process that occurs either under natural gravity or by coagulations. It was found that the oily and non-oily POME sediments have different sizes with nonspherical irregular shapes, and because of that, the aspect ratio (AR) and circularity shape factors were adopted to describe the shapes of these sediments. The results also indicate that the density of oily POME sediment decreases as the sediment size increases.